2016
DOI: 10.1111/ajo.12467
|View full text |Cite
|
Sign up to set email alerts
|

Association between pelvic floor disorder symptoms and QoL scores with depressive symptoms among pelvic organ prolapse patients

Abstract: A 'positive' screening for DS was associated with worse PFDI-20 and P-QoL scores despite no difference in objective measurements. It may be that depressed patients interpret their symptoms differently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 18 publications
1
26
0
1
Order By: Relevance
“…Prolapse may increase symptoms of depression, while symptoms of depression may impact health behavior, symptom burden, QoL, and functional impairment pre-and post-operatively [56]. Our research found that surgery leads to a dramatic improvement not only in condition-speci c QoL but also in depressive symptoms.…”
Section: Discussionmentioning
confidence: 52%
“…Prolapse may increase symptoms of depression, while symptoms of depression may impact health behavior, symptom burden, QoL, and functional impairment pre-and post-operatively [56]. Our research found that surgery leads to a dramatic improvement not only in condition-speci c QoL but also in depressive symptoms.…”
Section: Discussionmentioning
confidence: 52%
“…Patients with POP reported worse self-perceived BI, and poor BI is associated with depression and poor psychosocial functioning. Depression is also associated with developing severe POP symptoms, functional impairment, and impaired HRQoL [38]. Thus, depression has a bidirectional relation with QoL in that depression leads to poor QoL and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with POP reported worse self-perceived BI, and poor BI is associated with depression and poor psychosocial functioning. Depression is also associated with developing severe POP symptoms, functional impairment, and impaired HRQoL [38]. Thus, depression has a bidirectional relation with QoL in that depression leading to poor QoL and vice versa.…”
Section: Discussionmentioning
confidence: 99%